Prevalence of posterior crossbite among pacifier users: a study in the deciduous dentition - Scavone-Junior,Helio (2007)
The aim of this study was to evaluate the prevalence of posterior crossbite among children whose pacifier-sucking habit persisted until different ages. Children aged 3 to 6 years were randomly selected from public preschools in São Paulo, SP, Brazil. Their mothers were asked to complete a questionnaire on non-nutritive sucking behaviors. The sample consisted of 366 children assigned to 2 groups: control (n = 96) and pacifier users (n = 270). Pacifier users were further assigned to 3 subgroups, according to the age of habit persistence: P1 - until 2 years of age; P2 - between 2 and 4 years of age; and P3 - between 4 and 6 years of age. One dentist assessed the children for occlusal relationships through clinical examination. Associations between the age interval of habit discontinuation and the prevalence of posterior crossbite were analyzed using the chi-square test (p < 0.05). The prevalence of posterior crossbite was significantly higher among pacifier users (20.4%), compared to control children (5.2%), p < 0.01. Unilateral posterior crossbite was more prevalent than bilateral crossbite among pacifier users (9.8% versus 3.6%). Functional posterior crossbites were diagnosed in 3.1% of the control children and 7% of the pacifier users. The frequencies of posterior crossbite were notably high for children in the 3 pacifier subgroups, P1, P2, and P3, corresponding to 17.2%, 16.9%, and 27.3%, respectively. The high prevalence of posterior crossbite may be associated with pacifier-sucking habits that persisted after 2 years of age.